2022
DOI: 10.1186/s13020-022-00644-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ONT and CCS sequencing technologies on the polyploid genome of a medicinal plant showed that high error rate of ONT reads are not suitable for self-correction

Abstract: Background Many medicinal plants are known for their complex genomes with high ploidy, heterozygosity, and repetitive content which pose severe challenges for genome sequencing of those species. Long reads from Oxford nanopore sequencing technology (ONT) or Pacific Biosciences Single Molecule, Real-Time (SMRT) sequencing offer great advantages in de novo genome assembly, especially for complex genomes with high heterozygosity and repetitive content. Currently, multiple allotetraploid species ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While isoform expression patterns can be inferred with SRS technologies, it has many limitations that can be overcome using LRS (Hu et al, 2021; Stark et al, 2019). Through optimized circular consensus sequencing, LRS provides a reliable insight into the transcriptome, potentially offering full-length transcript resolution (Sharon et al, 2013; Zeng et al, 2022). LRS has been used to characterize expression patterns of isoforms of annotated genes in human cells, an example of which is expression of transposon-derived short isoform of IFNAR2 (Pasquesi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While isoform expression patterns can be inferred with SRS technologies, it has many limitations that can be overcome using LRS (Hu et al, 2021; Stark et al, 2019). Through optimized circular consensus sequencing, LRS provides a reliable insight into the transcriptome, potentially offering full-length transcript resolution (Sharon et al, 2013; Zeng et al, 2022). LRS has been used to characterize expression patterns of isoforms of annotated genes in human cells, an example of which is expression of transposon-derived short isoform of IFNAR2 (Pasquesi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to improve the accuracy of an ONT is to correct errors before assembly. However, due to the high error rates, ONT with R9 chemistry are not suitable for self-correction [28]. Another approach is to use correction tools such as Ratatosk which allow to polish ONT with NGS reads [29].…”
Section: Ont Based and Hybrid Assemblersmentioning
confidence: 99%
“…For example, when applied to the sequencing of the polyploid genome of Veratrum dahuricum , ONT produced ultra-long reads. However, by mapping the NGS reads against the ONT assemblies and a SMRT CCS assembly, researchers found that the coverage of three ONT assemblies ranged from 49.15% to 76.31%, much smaller than that of the SMRT CCS assembly (99.53%) ( Zeng et al., 2022 ). A hybrid sequencing approach seems to be a good resolution because it has been shown in many medicinal organisms ( Jain et al., 2018 ; Song et al., 2018 ; Wang et al., 2018 ) that combining NGS short reads with ONT can improve both the accuracy and completeness of obtained assemblies.…”
Section: Advantages and Challengesmentioning
confidence: 99%